Intrafractional motion in online-adaptive magnetic resonance-guided radiotherapy of adrenal metastases leads to reduced target volume coverage and elevated organ-at-risk doses - Hoegen-Saßmannshausen, Philipp; Hartschuh, Tobias P.; Renkamp, Claudia Katharina; Buchele, Carolin; Schlüter, Fabian; Sandrini, Elisabetta; Weykamp, Fabian; Regnery, Sebastian; Meixner, Eva; König, Laila; Debus, Jürgen; Klüter, Sebastian; et al. (Cancers, 2025)
Background/Objectives: Stereotactic body radiotherapy is frequently used in patients with adrenal metastases. Motion of adherent radiosensitive organs at risk (OARs) and tumors influence OAR toxicity and tumor control. Online-adaptive Magnetic Resonance-guided radiotherapy (MRgRT) can address and mitigate interfractional changes. However, the impact of intrafractional variations in adrenal MRgRT is unknown. Methods: A total of 23 patients with 24 adrenal metastases were treated with MRgRT. After daily plan adaptation and before beam application, an additional (preRT) 3d MRI was acquired. PreRT target volumes and OARs were retrospectively recontoured in 200 fractions. The delivered, online-adapted treatment plans, as well as non-adapted baseline plans, were calculated on these re-contoured structures to quantify the dosimetric impact of intrafractional variations on target volume coverage and OAR doses with and without online adaptation. Normal tissue complication probabilities (NTCPs) were calculated. Results: The median time between the two MRIs was 56.4 min. GTV and PTV coverage (dose to 95% of the PTV, D95%, and volume covered by 100% of the prescription dose, V100%) were significantly inferior in the preRT plans. GTV Dmean was significantly impaired in left-sided metastases, but not in right-sided metastases. Compared to non-adapted preRT plans, adapted preRT plans were still significantly superior for all GTV and PTV metrics. Intrafractional violations of OAR constraints were frequent. D0.5cc and the volume exposed to the near-maximum dose constraint were significantly higher in the preRT plans. The volume exposed to the D0.5cc constraints in single fractions escalated up to 1.5 cc for the esophagus, 3.2 cc for the stomach, 5.3 cc for the duodenum and 7.3 cc for the bowel. This led to significantly elevated NTCPs for the stomach, bowel and duodenum. Neither PTV D95%, nor gastrointestinal OAR maximum doses were significantly impaired by longer fraction duration. Conclusions: Intrafractional motion in adrenal MRgRT caused significant impairment of target volume coverage (D95% and V100%), potentially undermining local control. Frequent violation of gastrointestinal OAR constraints led to elevated NTCP. Compared to non-adaptive treatment, online adaptation still highly improved GTV and PTV coverage.